Exploring the customer's expectation towards shuttle service by KTMB / Noraini Ismail - Ismail, Noraini (2004)
This study will focus on customer's expectation towards shuttle service of KTMB. KTMB main target are those Malaysian working in Singapore. So, this will bring benefits to the consumers itself. The customers will not have to face the city's notorious traffic congestion. Therefore, the consumers will be able to use Shuttle Service as another mode of transport to Singapore. KTMB sees this as a big opportunity to extend its service as well as to capture the potential markets. For this purpose a structured questionnaire will be design to obtain all the relevant information in order to fulfill the research objectives. Actually, KTMB is still waiting for the approval of the Singapore Government.